Pharmacogenomics of MDR and MRP subfamilies. (1st December 2004) - Okamura, Noboru; Sakaeda, Toshiyuki; Okumura, Katsuhiko
Drug-metabolizing enzymes, drug transporters and drug targets play significant roles as determinants of drug efficacy and toxicity. Their genetic polymorphisms often affect the expression and function of their products and are expected to become surrogate markers to predict the response to drugs in individual patients. With the sequencing of the human genome, it has been estimated that approximately 500––1200 genes code for drug transporters and, recently, there have been significant and rapid advances in the research on the relationships between genetic polymorphisms of drug transporters and interindividual variation of drug disposition. At present, the clinical studies of multi-drug resistance protein 1 (MDR1, P-glycoprotein, ABCB1), which belongs to the ATP-binding cassette (ABC) superfamily, are the most comprehensive among the ABC transporters, but clinical investigations on other drug transporters are currently being performed around the world. MDR1 can be said to be the most important drug transporter, since clinical reports have suggested that it regulates the disposition of various types of clinically important drugs, but in vitro investigations or animal experiments have strongly suggested that the members of the multi-drug resistance-associated protein (MRP) subfamily can also become key molecules for pharmacotherapy. In addition to those, breast cancer resistance protein (BCRP, ABCG2), another ABC transporter, is well known as a key molecule of multi-drug resistance to several anticancer agents. However, this review focuses on the latest information on the pharmacogenetics of the MDR and MRP subfamilies, and its impact on pharmacotherapy is discussed.